Integrated Stage Dual Buck -Boost Fly Back Converter LED Driver - Subha Sharmini, Kannan; Gulati, Prateek; Jain, Ankit (International Journal of Engineering and Technology, 2018)
This paper presents a novel integrated stage converter configuration being applied as a LED driver. In order to prove the betterment of the topology, its performance is compared in terms of power factor, output voltage and settling time with three other randomly selected topologies: A single switch AC-DC LED driver based on boost fly back power factor correction converter with a lossless snubber, Integrated stage double buck- boost converter LED driver, Integrated stage LED driver based on buck-boost and class E resonant converter. As a consequence of relevant simulations of all the chosen topologies with resistance as the load, it is understood that Integrated buck boost fly back converter based LED Driver is beneficial as a compromise between all circuits. Hence the same is translated into an experimental prototype which is capable of a yield rated 45 V, 84.6 W and 1.88 A for a LED string load. Â